SYMBOLIC VIOLENCE IN RELIGIOUS DISCOURSE IN INDONESIA (International Conference on Social and Islamic Studies, 2021)
Religious discourse is one of the instruments that are often used by the dominant class (the majority, who are in power) to carry out a symbolic violence mechanism against the dominated class (the minority, who are ruled). For example, through religious discourses that seem plural and open, the power and domination of the dominant class are continuously perpetuated. This study aims to analyze the symbolic violence that occurs in religious discourse in Indonesia, especially in the study of religion, by reviewing the discourse of “agama vs. kepercayaan” and “moderasi beragama”. The symbolic violence referred to here is, according to Pierre Bourdieu's theory, violence that does not appear asviolence and is latent. Victims of this type of violence do not feel that they are victims ofviolence as if what happened was natural and it should have been. This study also argues that symbolic violence in religious discourse in Indonesia is widely produced in educational institutions, especially through the hands of academics, because through educational institutions, discourses of “agama vs. kepercayaan” and “moderasi beragama” are formulated and then implemented in government policies, as if the discourse has accommodated all religions and beliefs, but only perpetuates the way of thinking and tastes of the dominant class. In short, this study argues that religious discourses such as “agama vs. kepercayaan” and “moderasi beragama” are produced by the dominant class through educational institutions and so on and produce symbolic violence.